Harnessing Renewable Energy for Special Events Using Image processing, Remote Sensing and GIS techniques - Sabah, Mustafa; Jaber, Hassan; Fadel, Ibtisam; Razzaq, Ban Abdul; Abbas, Sundus Abdul (Iraqi Journal of Science, 2025)
Photovoltaic cells are among the most important and common renewable energy sources, especially in areas with high solar radiation, like Iraq, millions of pilgrims travel on foot every Hijri year in the month of Safar from various provinces of Iraq and from different countries to commemorate the Arbaeen anniversary of Imam Hussein by heading towards the Holy Karbala. During the pilgrimage, numerous organizations or stations (processions) are set up on both sides of the pilgrim’s path to provide service to pilgrims. This study highlights the possibility of providing electric energy using renewable energy to these processions along the Baghdad-Karbala Road. The study aims to provide electric energy using renewable sources to these processions along the Baghdad-Karbala Road. Photovoltaic cells are among the most important and common renewable energy sources, especially in areas with high solar radiation, like Iraq. The best sites for solar cell stations will be determined using remote sensing applications and Geographic Information Systems (GIS) by analyzing satellite images (Sentinel 2 and ALOS PALSAR) to calculate the necessary criteria. The hierarchical analysis process is used to determine the optimal locations for photovoltaic cells and to estimate the energy production rate using MATLAB simulations. This research provides valuable insights into the possibility of providing Husseini Camps (processions) with clean energy along the Baghdad-Karbala Road by taking advantage of solar radiation. This study provides a comprehensive and practical approach to ensure sustainable energy supply for the processions, and the results can guide decision-making and development of energy infrastructure in the future, as well as work on similar initiatives in other regions. The results showed that the study area receives high solar radiation, that a low slope characterizes the area’s nature, and that the percentage of land suitable for constructing photovoltaic stations is more than 80%. Thus, it is possible to establish more than one photovoltaic station to supply the main electricity grid with renewable energy.